Potential Utilisation and Distribution of Professional Zakat at the Ministry of Religious Affairs of North Sumatra - Syabrun Jukhoir; Ansari Yamamah; Mhd Yadi Harahap (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
The National Amil Zakat Agency is given the authority as the national zakat manager, and also has the right to verify the establishment of Amil Zakat Institutions and Zakat Collection Units, this is stated in Law No. 23 of 2011, Professional Zakat in the perspective of this Law, there is an affirmation that professional zakat has been officially and legally, binding and juridically institutionalised in Indonesian regulations. Civil Servants are a source of zakat income for the National Amil Zakat Agency at the Ministry of Religious Affairs of North Sumatra Province. This study aims to analyse the potential utilization and distribution of professional zakat and management in the management of zakat for the profession of Civil Servants in the National Amil Zakat Agency, as well as to analyse the supporting and inhibiting factors in zakat management research. The method in this research is descriptive qualitative research. Data collection techniques are interviews, observation, and documentation, as well as literature studies through national journals. National Amil Zakat Agency information data about the potential utilisation and distribution of professional zakat. Conclusion The results of the study convey that one of the potential utilisation and distribution of professional zakat has not been carried out effectively due to the absence of an independent control board in the structure of the National Amil Zakat Agency and the less than optimal implementation of professional zakat collection with supporting factors and solutions to existing obstacles in professional zakat management activities.